RELATIONSHIP OF PARENTS ATTENTION BY STUDENT LEARNING RESULT CLASS V SD NEGERI 101800 DELI TUA - Halimatussakdiah Nasution (Universitas Negeri Medan, 2017)
Abstract: Relationship of Parent Attention with Student Result of Grade V of SD Negeri 101800 Deli Tua. The purpose of this study is to determine the relationship of parents 'attention to the results of students' learning grade V SD Negeri 101800 Deli Tua. This research was conducted at SD Negeri 101800 Deli Tua with population of 45 people and sample with 45 respondents. The sampling technique is done by total sampling while the instrument used to measure the attention of the parents is a questionnaire with the number of 30 items declared valid. Test validity was tested using product moment correlation technique with result 21 stated valid, while test reliability was tested using alpha with result 1,026 at significant level 95% with alpha 5%. Data analysis technique using Product Moment correlation sedek hypothesis using t test. Result of calculation of correlation coefficient indicate that rtabel at 5% significant level equal to 0,301 while rhitung equal to 0,319 are in positive direction. Thus it can be seen that the rhitung is greater than the rtabel at a significant level of 5%. While the hypothesis by using t test obtained rhitung of 2.206 and rtabel 2.016.Keywords: Attention Parents, Student Learning OutcomesAbstrak : Hubungan Perhatian Orangtua Dengan Hasil Belajar Siswa Kelas V SD Negeri 101800 Deli Tua. Tujuan penelitian ini adalah untuk mengetahui hubungan perhatian orangtua dengan hasil belajar siswa kelas V SD Negeri 101800 Deli Tua. Penelitian ini dilakukan di SD Negeri 101800 Deli Tua dengan populasi sebanyak 45 orang dan sampel dengan 45 responden. Teknik pengambilan sampel dilakukan dengan total sampling sedangkan instrument yang digunakan untuk mengukur perhatian orang tua adalah angket dengan jumlah 30 butir dinyatakan valid. Validitas tes diuji menggunakan teknik korelasi product moment dengan hasil 21 dinyatakan valid, sedangkan reliabilitas tes di uji menggunakan alpha dengan hasil 1,026 pada taraf signifikan 95% dengan alpha 5%. Teknik analisis data dengan menggunakan korelasi Product Moment sedankan hipotesis menggunakan uji t. Hasil perhitungan koefisien korelasi menunjukkan bahwa rtabel pada taraf signifikan 5% sebesar 0,301 sedangkan rhitung sebesar 0,319 berada pada arah yang positif. Dengan demikian dapat diketahui bahwa rhitung lebih besar dari rtabel pada taraf signifikan 5%. Sedangkan hipotesis dengan menggunakan uji t diperoleh rhitung sebesar 2,206 dan rtabel 2.016.Kata Kunci : Perhatian Orangtua, Hasil Belajar Siswa